A COMPARISON OF TYPES OF DOMESTIC VIOLENCE IN ZORA NEALE HURSTONâ€™S â€œSWEATâ€ AND IN SANDRA CISNEROSâ€™S â€œWOMAN HOLLERING CREEKâ€ - Mashbahah Baroroh; Linusia Marsih (Anaphora : Journal of Language, Literary, and Cultural Studies, 2018)
. This study reveals the types of domestic violence in â€œSweatâ€ by Zora Neale Hurston and â€œWoman Hollering Creekâ€ by Sandra Cisneros. The discussion will involve the types of abuse, the reactions of the victims, and the similarities and differences about the abuse in the two selected short stories. This study is designed to interpret phenomena of life associated to domestic violence reflected in the selected stories. Thus, this is a qualitative study. As the discussion is focused on the charactersâ€™ psychological aspects, the extrinsic approach is applied.Â  The study finds out that the types of domestic violence that exist in the stories are emotional/psychological violence and physical violence and the victims of the abuse response somewhat differently to the abuse. The reactions of the abuse victim in Hurstonâ€™s â€œSweatâ€ include taking the violent silently and then to be moved to fight back, and the reactions of the abuse victim in Cisneros â€œWoman Hollering Creekâ€ include Â taking the violent silently and then making an effort to be free from the abuse by getting help from other people. The analysis also shows that the two short stories contain both similarities and differences.